Evaluation of The Orthopedic Hospital Website's Performance Using User Acceptance Testing - Resad Setyadi; Aedah Abd. Rahman; Toni Anwar (Applied Information System and Management (AISM), 2025)
User Acceptance Testing (UAT) is essential for ensuring a system meets the real-world needs of its users. Unlike traditional testing that prioritizes technical accuracy, UAT focuses on usability and overall user satisfaction. For the Orthopedic Hospital's website, UAT served as the primary evaluation method, targeting its core user groups—patients, staff, and stakeholders. The testing process followed the ISO 9126 software quality standards, evaluating the website across key dimensions such as functionality, reliability, usability, efficiency, maintainability, and portability. A Likert scale was used to capture structured user feedback, providing quantifiable insights into user perceptions. This combined approach allowed for a well-rounded assessment, balancing technical quality with user experience. Results indicated a high satisfaction rate of 92.7%, reflecting strong approval of the website’s design and functionality. However, the evaluation also pointed to areas for enhancement. The online registration process, for example, could be simplified to improve ease of use and task completion. While the results are promising, continued improvement is vital—especially in healthcare, where user experience directly affects patient outcomes and service efficiency. To maintain alignment with evolving user needs and technologies, ongoing UAT cycles should be integrated into the hospital’s digital strategy. Leveraging ISO 9126 standards and user-centered tools like the Likert scale will ensure the website remains effective, accessible, and responsive to its users.